Geoengineering Characteristics of Site Soil Profile Analysis using Cone Penetration Tests Data - Munirwan, Reza Pahlevi; Devi Sundary; Munirwansyah; Banta Chairullah; Jaya, Ramadhansyah Putra (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Classification and stratification of subsurface soils are critical aspects for a geotechnical site assessment to design and construct geotechnical structures. A probabilistic interpretation method is devised to adequately account for the uncertainty associated with subsurface soil categorization and stratification based on cone penetration test (CPT) data. CPT data is frequently directly employed in the construction of deep and shallow foundations, as well as a range of other purposes. It is advantageous to employ CPT data to create stratigraphic profiles as well, in order to generate more cost-effective designs. The method is demonstrated using CPT data from several locations in the Banda Aceh area. From limited CPT data, the approach accurately identifies subsurface soils in a 2D vertical cross-section. The objectives of this paper are to utilize CPT data to examine the soil profile in Banda Aceh, Indonesia. Additionally, soil parameters must be evaluated to obtain a better knowledge of Banda Aceh's soil conditions. The evaluation indicates that the average depth of the hard layer in the Kuta Alam District ranges from 5 to 8 meters beneath the ground surface. However, at certain locations, the hard soil stratum reaches a depth exceeding 18 meters. The findings are expected to be one source for determining the preliminary soil profile condition in Banda Aceh before doing additional soil investigation for construction design requirements.